The feasibility of electrical generation by using tidal method - Rosmin, Norzanah; Zakaria, Muhammad Pahlavi (Faculty of Electrical Engineering, 2006)

(untitled)
This paper proposes an offshore generation method for tidal electrical generation system. Generating electrical energy by using tidal effect is another source of a renewable energy without giving any negative impacts on environment. The theory of tidal energy is that it cycle for 24 hours without stopping. Since tidal generation depends on height, then the most critical requirement for generating electrical energy by using tidal effect is the differences between low tide and high tide. The suitable mathematical equations are used to evaluate the performance of the proposed approach compared to the conventional scheme. The simulation results show the ability of generating electrical energy by using offshore tidal generation scheme. The feasibility of this system was analyzed at Sejingkat, Sarawak. This location is chosen because it has the largest differences between low tide and high tide. Offshore generation at Sejingkat, Sarawak offers 6.257 MW as a mean of potential energy per month. Maximum potential energy can be generated in January whereas the minimum in August, which is about 6.543MW and 5.963MW, respectively. Thus, the proposed scheme shows that the offshore tidal generation system at such location is feasible based on the stable monthly potential energy.